Do suicide attempters and suicide ideators differ in capability for suicide?. (May 2019) - Paashaus, Laura; Forkmann, Thomas; Glaesmer, Heide; Juckel, Georg; Rath, Dajana; Schönfelder, Antje; Engel, Philipp; Teismann, Tobias
Highlights: Objective pain persistence as a dimension of capability for suicide was assessed using a pressure algometer. Suicide ideators and suicide attempters in an inpatient sample did not differ regarding their acquired capability for suicide such as fearlessness about death, subjective pain tolerance and objective pain persistence Further effort is needed to clearly understand what distinguishes suicide attempters from suicide ideators Abstract: Suicide ideation is a prerequisite for suicide attempts. However, the majority of ideators will never act on their thoughts. It is therefore crucial to understand what differentiates those who consider suicide from those who attempt suicide. The aim of this study was to investigate the role of different aspects of capability for suicide (fearlessness about death, subjective pain tolerance, objective pain persistence) in differentiating suicide ideators from suicide attempters, single attempters from multiple attempters and recent attempters from distant attempters. A total of 308 psychiatric inpatients (53.6% female; age: M =36.92, SD =14.30) suffering from suicide ideation with or without lifetime suicide attempts were compared regarding fearlessness about death, subjective pain tolerance and objective pain persistence (assessed with a pressure algometer). No differences in fearlessness about death, subjective pain tolerance and objective pain persistence were found in suicide ideators vs. attempters, single vs. multiple attempters and recent vs. distant attempters. It might be presumed that fearlessness about death, subjective pain tolerance and objective pain persistence do not offer useful information for the differentiation between suicide ideators and attempters, however, there are several limitations to take into account. Further effort is needed to understand more clearly what differentiates suicide ideators from suicide attempters.